Study on TEA Encryption for Public Communication Network Wireless Remoter - Ge, Yue Tao; Yin, Xiao Tong; Liu, Xiao Ming (Applied Mechanics and Materials, 2014)
In order to realize wireless remoter not only securely but also quickly data transmission in the public communication network, the Tiny Encryption Algorithm (TEA) encryption and decryption algorithm is studied in this paper and the properties of TEA are analyzed. According to communication protocol of remoter, encryption and decryption program process are designed. Because of TEA encryption, remoter transmitter and receiver can communicate strongly in the public communication network.